Customized MFM probes based on magnetic nanorods. Issue 18 (29th April 2020) - Jaafar, Miriam; Pablo-Navarro, Javier; Berganza, Eider; Ares, Pablo; Magén, César; Masseboeuf, Aurélien; Gatel, Christophe; Snoeck, Etienne; Gómez-Herrero, Julio; de Teresa, José María; Asenjo, Agustina
Abstract : Focused Electron Beam Induced Deposition (FEBID) for magnetic tip fabrication is presented in this work as an alternative to conventional sputtering-based Magnetic Force Microscopy (MFM) tips. Abstract : Focused Electron Beam Induced Deposition (FEBID) for magnetic tip fabrication is presented in this work as an alternative to conventional sputtering-based Magnetic Force Microscopy (MFM) tips. FEBID enables the growth of a high-aspect-ratio magnetic nanorod with customized geometry and composition to overcome the key technical limitations of MFM probes currently on the market. The biggest advantage of these tips, in comparison with CoCr coated pyramidal probes, lies in the capability of creating sharp ends, nearly 10 nm in diameter, which provides remarkable (topographic and magnetic) lateral resolution in samples with magnetic features close to the resolution limits of the MFM technique itself. The shape of the nanorods produces a very confined magnetic stray field, whose interaction with the sample is extremely localized and perpendicular to the surface, with negligible in-plane components. This effect can lead to a better analytical and numerical modelling of the MFM probes and to an increase in the sensitivity without perturbing the magnetic configuration of soft samples. Besides, the high-aspect ratio achievable in FEBID nanorod tips makes them magnetically harder than the commercial ones, reaching coercive fields higher than 900 Oe. According to the results shown, tips based on magnetic nanorods grown by FEBID can be eventually used for quantitative analysis in MFM measurements. Moreover, the customized growth of Co- or Fe-based tips onto levers with different mechanical properties allows MFM studies that demand different measuring conditions. To showcase the versatility of this type of probe, as a last step, MFM is performed in a liquid environment, which still remains a challenge for the MFM community largely due to the lack of appropriate probes on the market. This opens up new possibilities in the investigation of magnetic biological samples.